2013
DOI: 10.5402/2013/450948
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Extraction Optimization and Analysis of Flavonoids from the Flowers of Tabernaemontana heyneana by High Performance Liquid Chromatography Coupled to Diode Array Detector and Electron Spray Ionization/Mass Spectrometry

Abstract: Flavonoids are exploited as antioxidants, antimicrobial, antithrombogenic, antiviral, and antihypercholesterolemic agents. Normally, conventional extraction techniques like soxhlet or shake flask methods provide low yield of flavonoids with structural loss, and thereby, these techniques may be considered as inefficient. In this regard, an attempt was made to optimize the flavonoid extraction using orthogonal design of experiment and subsequent structural elucidation by high-performance liquid chromatography-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…For the studied target compounds (Tr and Ph), there are many scientific references suggesting a significant degradation rate at ethanol's boiling point as the time-cycles are prolonged. 35 Therefore, to optimize the number of cycles and consequently measure the total content of Tr and Ph at its maximum, the time-cycle (note that each cycle accounts approximately for a 30 min period) of SE for G. lucidum was monitored. Fig.…”
Section: Extraction Efficiency By Using the Soxhlet Techniquementioning
confidence: 99%
“…For the studied target compounds (Tr and Ph), there are many scientific references suggesting a significant degradation rate at ethanol's boiling point as the time-cycles are prolonged. 35 Therefore, to optimize the number of cycles and consequently measure the total content of Tr and Ph at its maximum, the time-cycle (note that each cycle accounts approximately for a 30 min period) of SE for G. lucidum was monitored. Fig.…”
Section: Extraction Efficiency By Using the Soxhlet Techniquementioning
confidence: 99%
“…Extended extraction time has also led to an increase of adhesion of diffused particles (antioxidant compound) around the walls of the supporting material like glass or plastic tubes that may interrupt the process of extraction. Hence, this can be used to explain the insignificant effect of time on antioxidant activity in this study [31].…”
Section: Analysis Of Antioxidant Activitymentioning
confidence: 95%
“…A slight decrease of antioxidant activity can be clearly seen at 15 minutes of extraction which probably explained by the presence of synergistic effect of other involved parameters. Besides, the decomposition of antioxidant compound may happen because of the thermal-based oxidation reaction that occurs during the extraction process [31]. Meanwhile, the statistical analysis has revealed that there was a significant effect of extraction temperature (p < 0.05) on antioxidant activity and there was no significant effect of extraction time (p > 0.05) on antioxidant activity.…”
Section: Analysis Of Antioxidant Activitymentioning
confidence: 99%
“…Total flavonoid contents of MLEAV and PLEAV was estimated by the method [16]. An aliquot of each extract 0.1 ml was taken into a test tube and made up to 5 ml with distilled water.…”
Section: Estimation Of Total Flavonoids Contentsmentioning
confidence: 99%